Defence industries and open innovation: ways to increase military capabilities of the Portuguese ground forces - Reis, ‪João Carlos Gonçalves dos (2022)
The European Defence Industry is undergoing profound changes. Industrial activity is now operating on a quintuple helix innovation model with the deep involvement of universities and governments in innovation. In addition, military innovations are being transferred to civil society, with increasing attention paid to the environment. In the first stage, we report on the state-of-the-art of existing research using PRISMA protocol. The PRISMA technique is widely accepted by the academic community for its ability to discover concepts, ideas, and debates about the defence industry. In the second stage, we present a case study involving the Portuguese Defence Industry, for which multiple data collection sources were used to ensure triangulation and corroboration. The results show that, in the light of the quintuple helix innovation model, it was possible to bring applications from theoretical discussion to real life. Moreover, within the scope of the triple helix, it was possible to develop, produce and test military products, allowing to improve the military capacity of ground forces. In the future, ecological concerns will likely increase, so we suggest a greater focus on this area of research. KEYWORDS : Defence industry; open innovation; ground military forces; quintuple helix